Identification of Qualitative and Quantitative Characteristics of Male Bali Cattle in Dompu District - Gita Nabilla Islami; Lalu Muhammad Kasip; Tapaul Rozi (Jurnal Biologi Tropis, 2023)
Livestock identification is a form of recording that must be done to provide information about individual livestock. This study aimed to identify the qualitative and quantitative characteristics of male bali cattle in Dompu Regency. Data analysis was carried out using statistics descriptive, using the average, standard deviation, and coefficient of variation. One hundred twenty male bali cattle aged 1-36 months were used as samples. The results showed the frequency of each feature was 47.5% light brown fur color, 32.5% dark brown, and 20% black. The eel line was 40% thick line, 15% medium line, 25% thin line, and 20% did not have eel line. The metatarsal color was 87.5% white with a firm border and 12.5% white with an indistinct border. The rump color was 82.5% white with a firm boundary and 17.5% white with an indistinct boundary. The tail feather color was 37.5% black-brown, 32.5% brown, and 30% black. Furthermore, the measurement results obtained for quantitative properties were 113.8 ± 10.0 for body length, with a 8.8% coefficient of variation. Chest circumference were 147.2 ± 11.8, with a 8.0% coefficient of variation. Back height were 112.0 ± 7.9, with a 7.1% coefficient of variation. Hip height were 115.8 ± 8.4, with a 7.2% coefficient of variation. Body weight were 287.6 ± 40.1, with a 14.0% coefficient of variation. The study results show that the male bali cattle characteristics at Dompu Regency are relatively heterogenous, both qualitatively and quantitatively.